Development of Digital Comic Media IPAS Based on LVEP to Enhance Global Diversity Character in Grade V Elementary School - Ira Setyawati; An-Nisa Apriani; Indah Perdana Sari; Ruwet Rusiyono (IJCAR: Indonesian Journal of Classroom Action Research, 2026)
This study aims to create a digital comic medium utilizing the Living Values Education Program (LVEP) to foster global diversity character in fifth-grade elementary students. The objective is to nurture students' potential in personality, morals, skills, and spiritual aspects. Introduced by Indonesia’s Minister of Education and Culture, Nadiem Makarim, in April 2021, the "Merdeka Belajar" Curriculum (Kumer) focuses on character education through the Pancasila Student Profile (P3) and encourages student autonomy in learning. The research employs the 4D development model: definition, design, development, and dissemination. Validation by media and material experts showed positive feedback and acceptance by teachers and students, affirming the medium's effectiveness in promoting global diversity character. This medium is expected to contribute to innovative learning methods and support the improvement of character education quality in Indonesia. Further development and implementation are anticipated to enhance efforts in fostering global diversity character among students.